An Analysis of the Development of China's Commercial Banks under the Structural Reform of the Supply Side - Zhu, Chen; Chen, Liping (Journal of Accounting, Business and Finance Research, 2018)
In recent years, with the acceleration of interest rate marketization in China, commercial banks are increasingly facing the business environment of increasing interest rate fluctuations, intensified competition among industries, and slowing down the growth of profitability. At the same time, in the past few years, the hidden credit risks behind the large-scale credit investment and high profits are gradually exposed, and the non-performing loan rate is rising. With the increasingly obvious drawbacks of demand-side management, supply-side reform emerges as the times require. Advocating innovation, adapting to consumption upgrading and guiding the optimization of export structure are its obvious advantages. As one of the main economic bodies, commercial banks should also clearly judge the current historical stage of their own. With the end of extensive economic growth, the expansion of commercial banks has ended, and a new historical turning point has arrived. The implementation of the structural reform on the supply side has put forward more explicit and specific requirements for the financial innovation of commercial banks. In this reform, commercial banks need to gradually establish a set of mechanisms, products and risk prevention system adapted to the new normal situation, and be able to flexibly use the relevant results to prevent and defuse the production capacity. This paper tries to analyze the opportunities and missions faced by commercial banks under the background of structural reform on the supply side, optimize the traditional development structure, sort out a new development framework, and give corresponding policy recommendations. We believe that commercial banks should take the initiative to support the supply-side reform while welcoming new opportunities for development. They should vigorously promote the growth of entrepreneurship finance, accelerate the development of Internet finance, dig deep into changes in customer demand, actively develop green finance, and optimize and adjust the credit structure of banks.